Mechanical characterisation of PEEK-HA composite as an orthopaedic implant. Issue 3 (3rd July 2022) - Dey, S. K.; S, Sujith Kumar; Sen, I.; Samanta, S.
ABSTRACT: Nowadays research in the biopolymers is prominent area for research in medical fields. The metallic implants are used in many numbers for the orthopaedic surgeries. But some unavoidable issues are arising after surgeries like stress-shielding, osteogenesis imperfection, etc. To overcome such issues, re-surgery is only one painful option available for the patient. Sometimes, this option is not feasible for the weak and old patients, which results in increased life risk in such situation. Hence, a biopolymer may be the best solutions to eliminate such problems. Polyether ether ketone (PEEK) and hydroxyapatite (HA) are having biocompatible characteristic with different mechanical properties. Hence in this paper, three different compositions of PEEK-HA are considered and the composites were prepared using compression moulding technique. To compare the mechanical properties for different compositions of PEEK-HA, the porosity and tensile strength were calculated. Unlike the other techniques, the fracture toughness was evaluated through J-integral method to ensure the matching of the cracking phenomenon with the human bone. Tribological properties, for example, wear resistance and plasticity index for all compositions of PEEK and HA were executed in both static and dynamic mode. The result reveals that PEEK5HA can be used for the possible bone replacement.